Cooperative intermolecular S–Cl⋯O and F⋯F associations in the crystal packing of α, ω-di(sulfonyl chloride) perfluoroalkanes, ClSO2(CF2)nSO2Cl, where n = 4, 6. (2nd May 2018) - Liu, Xiaolin; McMillen, Colin D.; Thrasher, Joseph S.
Abstract : Halogen bonding between neighboring sulfonyl chloride groups and short fluorine–fluorine contacts supports crystal formation in the title compounds. Abstract : Single-crystal, X-ray crystallographic studies of ClSO2 (CF2 )4 SO2 Cl and ClSO2 (CF2 )6 SO2 Cl reveal the first examples of S–Cl⋯O halogen bonding complemented by short F⋯F contacts between neighbouring chains that result in stabilized crystals. These compounds allow the study of intermolecular associations involving halogens where hydrogen bonding cannot be operative.